Informing decisions making on investments in agricultural research, resource management, and infrastructure through engagement with USAID - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
In 2017 IFPRI published a study/report on the use of Quantitative Foresight Modeling to inform the CGIAR Research Portfolio. The study, led by EPTD in collaboration with CGIAR and external partners, was originally commissioned and funded by the United States Agency for International Development (USAID). After completion, USAID showed a keen interest in using the results of the analysis to inform the strategic thinking of the USAID Bureau on Food Security (BFS) on questions related to investments toward poverty reduction.